The marginal social cost of road and rail: Implications for rail investment and pricing - Al-Tony, Fathy El-Sayed (Cranfield University, 1995)
An important issue for transport policy is whether more investment should be devoted to rail schemes and less to road schemes and vice versa. This raises the problem of comparing the returns from investments in the two modes currently assessed on a different basis - road schemes are appraised on a Cost Benefit Analysis (CBA) basis, whereas rail schemes are assessed on a Financial Analysis (FA). This study is a step in the direction of identifying the difference between the two techniques (CBA and FA) of appraisal in general and in case of rail investment in particular, and examining the implications of the use of the two different techniques in assessing the investment in road and rail. In addition, the study develops a methodology for assessing rail investment schemes that could be consistent with the cost benefit analysis being used in assessing road investment projects. The differences between CBA and FA are identified. The current practice of assessing road and rail investment schemes is examined and the weaknesses are outlined. The potential implications of assessing road and rail investment on different criteria are explored. Previous rail investment studies where both CBA and FA were undertaken are reviewed and discussed to explore how the task of CBA were carried out to rail schemes and to show the difference with the current study approach. The study framework of rail scheme appraisal is identified to include four elements of impacts. These are; financial impacts to the rail operator (producer surplus), rail user benefits (consumer surplus), non-user benefits, and other impacts on other bodies in the society (tax adjustments). Non-user benefits concerned by the study are road congestion time, noise, air pollution, accidents, and vehicle operating costs. Road congestion time, noise and air pollution are identified as externalities, while accidents and vehicle operating costs are dealt with as cases of cost misperception. The five items of non-user benefits are measured at the margin in a process to identify the Marginal Social Cost (MSC) of travel as a function of the road type alternative. Eight types of road are identified for the study to represent the entire UK road network. The measurement process of non-user benefits incorporates the variation in traffic over time and place. This is carried out by incorporating four traffic distributions in the calculation process. The distributions of traffic reflect traffic variations from hour to another (24 hours) throughout the day, from day to another (7 days) throughout the week, from month to another (12 months) throughout the year and from location to another throughout the UK entire road network. The implications of the study findings are explored. Three undesirable implications are identified. These are welfare losses to the society, lower share for rail travel, and investment bias towards roads. Three policy options are put as a solution. These are, pricing road and rail services according to the MSC, subsidising public transport, and applying a consistent appraisal method for road and rail investment. The contribution of these options towards achieving a sustainable balance between road and rail as well as their applicability in practice are examined. At the end some improvements and attached areas of further research are suggested.